Effect of Absurdity in Advertising on Brand Recall - Kansal, Purva; sharma, Himanshu R. (Indian Journal of Marketing, 2011)
Drawing insights from a survey of 120 young respondents, this article explores Indian youth's perspectives about absurdity in advertising across likeability, believability, trustability and purchasability. The paper first discusses the effect of absurdity on brand recall of the respondents followed by analysis of brand recall of absurd advertisements with likeability, believability, trustability and purchasability. Results demonstrate that there was a strong correlation between brand recall of absurd advertisements and entertainment value of an advertisement. The analysis highlighted that respondents did not consider absurd advertisements to impart any real information about the product and no correlation was found between recall value of absurd advertisements and believability and trustability. However, considering the strong correlation between other dimensions, among themselves, the stress on absurdity alone is a problematic trend in modern advertising.